Language transfers in third language acquisition of Chinese by intermediate level German and English native speakers: evidence from a behavioral experiment online - Wang, Ziqi; Xu, Caihua (Frontiers in Psychology, 2024)
The paper investigates language transfers in third language acquisition of Chinese by native German and English speakers at intermediate level. Subjects are divided into two groups and complete a Grammaticality Judgment and Correction Task through a behavioral experiment online. The results from multiple sources show that: (1) both L1 and L2 are sources of language transfers and the perceived crosslinguistic similarity of abstract structural properties serves as the main reason; (2) language transfers can be non-facilitative on L3 learning; (3) as L3 proficiency level improves, the less likely learners are to be affected by non-facilitative language transfers in L3 learning, but it may not disappear completely; (4) the background language with higher proficiency level is more likely to impose language transfers in L3 learning. The research suggests that language transfers in TLA are simultaneously regulated by a number of factors, such as similarities of abstract structural properties between background languages and L3, as well as language proficiency levels. At the end, we discuss the application of the results to Chinese language teaching.